OP94 Patient experiences of hospital care during the COVID-19 pandemic in Ireland. (26th August 2022) - Rohde, Daniela; Foley, Conor; Drummond, Linda; Murphy, Roisin; O'Carroll, Tracy; Flynn, Rachel
Abstract : Background: The COVID-19 pandemic has greatly impacted the delivery of healthcare services. It is important to understand its effects on various aspects of patient care, including patient experience. The aim of this mixed methods study was to explore patient experiences of hospital care during the COVID-19 pandemic in Ireland, using data collected as part of the National Inpatient Experience Survey (NIES) 2021. Methods: The NIES is a repeat cross-sectional survey of inpatient experiences in all 40 public acute hospitals in Ireland. Patients were eligible to participate if they spent 24+ hours in hospital and were discharged in September 2021. Seven questions addressed experiences specific to the pandemic, including a free-text question on how the pandemic affected patients' care. Comparisons of question ratings between 2019 and 2021 were conducted using t-tests, with a Bonferroni-adjusted alpha level of p <.0002. Effect sizes ( d ) are reported. Qualitative data were analysed using thematic analysis. Results: 10, 743 patients participated (42% response rate). While 67.6% indicated that they did not feel at risk of catching COVID-19 while in hospital, 31.1% definitely, or to some extent, felt at risk. A third of patients (34.6%) reported that staff always helped them to keep in touch with family. Small but statistically significant differences in ratings between 2019 and 2021 were found for some items, with questions on the opportunity for family members to talk to a doctor ( d =-0.328), provision of information to family members ( d =-0.136), and being able to find a member of staff to talk to about worries and fears ( d =-0.167) recording the biggest decreases in ratings. Question scores for cleanliness of wards ( d =0.063) and bathrooms ( d =0.075), and privacy during examination or treatment in the emergency department ( d =0.085) improved significantly. Patients commented on their appreciation of staff and the care received, but missed being able to have visitors, with visiting restrictions posing particular challenges for patients with sensory, physical or cognitive impairments. Some comments highlighted postponed care due to COVID-19, and concerns over being in close proximity with potentially infectious patients. Conclusion: Given the unique challenges experienced by acute healthcare services during the COVID-19 pandemic, any comparisons with pre-pandemic patient experiences should be interpreted with caution. Continuing to gather patient feedback during a pandemic presents a unique opportunity to understand the resilience of healthcare systems as they continue to operate under unprecedented pressure, with the potential to inform responses and delivery of care during future pandemics or other emergencies.